Load control in distributed database based multistage decision-making system - Borzemski, Leszek (Zielona Góra: Uniwersytet Zielonogórski)
In shared database management systems there is a need for load control to improve distributed system utilization. It is shown how this aim can be achieved in the case of a distributed database developed for supporting a decision-making distributed system where decisions are based on a common decision tree.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka